Update on the global burden of acute viral hepatitis in 2021: addressing health inequalities - Lei Zhang; Ting Wang; Shan Zhou; Shengpeng Li; Ting Mo; Shuanghua Wu (Frontiers in Public Health)
BackgroundThe strategy for eliminating viral hepatitis is at a critical juncture, necessitating an updated assessment of global incidence trends.MethodsData on the incidence of four types of acute viral hepatitis (AVH), namely, acute hepatitis A (AHA), acute hepatitis B (AHB), acute hepatitis C (AHC), and acute hepatitis E (AHE), were sourced from the Global Burden of Disease (GBD) Study 2021. The annual percentage change is utilized to elucidate temporal trends, whereas health inequalities and frontier analysis serve to evaluate global health equity and quantify disparities in burden among countries.ResultsIn 2021, the estimated global incidence for AVH was as follows: AHA (160.86 million), AHB (63.53 million), AHE (19.37 million), and AHC (7.01 million). From 2000 to 2021, the age-standardized incidence rates (ASIR) for four types of AVH demonstrated a declining trend, with AHB showing the most significant decrease. It is anticipated that the incidence rates for AHA, AHB, and AHC will continue to decline over the next 15 years; however, the incidence rate of AHE is projected to increase. In 2021, the incidence of AVH displayed a significant negative correlation with the Socio-Demographic Index (SDI), but health disparities between countries have diminished. Countries with the highest potential for elimination of AHB are primarily situated in low and low-middle SDI regions, whereas those for AHA are concentrated in high and high-middle SDI regions. Furthermore, countries with the largest disparities in AHC and AHE were dispersed.ConclusionAlthough global incidence of AVH is decreasing, it remains a serious public health challenge. Reducing health disparities is crucial for the elimination of viral hepatitis.